The Influence of CH3NH3I/ Pbi2 Ratio on The Absorption and Electrical Characteristics of Perovskite/Polymer Solar Cell - Shobih Shobih; Erlyta Septa Rosa; Endang Lestari (Institut Teknologi Sepuluh Nopember, 2017)
In this paper, we report a simple solution processed perovskite/polymer solar cell using CH3NH3PbI3 as an absorber, PCBM (6,6 phenyl C61-butyric acid methyl ester) as an electron transport layer, and PEDOT:PSS (poly (3,4-ethylene dioxy thiophene):poly(styrene sulfonate)) as a hole transport layer. The absorber solution was prepared by mixing of CH3NH3I (methyl ammonium iodide) with PbI2 (lead iodide) in DMF (dimethyl formamide) solvent. The absorber, electron transport, and hole transport layers are deposited by spin coating of the solutions. In order to obtain the optimum optical and electrical characteristics, the mixture of CH3NH3I and PbI2 are varied by the molar ratio of 1:1, 1:3, and 3:1, respectively. Because of CH3NH3PbI3 layer degrades, the fabricated cells have low performance. However, the cell using a molar ratio of 1:1 CH3NH3I and PbI2 gives the best electrical characteristics, results in an open circuit voltage of 0.04 V, a short circuit current density of 0.08 mA/cm2, and a power conversion efficiency of 0.002 %.